ANALISIS PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - ,Fitri, Anisa Sholeha , Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of firm size, profitability and leverage on earnings management. This type of research is quantitative research. The population in this study includes all companies in the transportation sub-sector. The sample in this study amounted to 23 companies. The sampling method used in this study was purposive sampling, while the data processing method used in this study was multiple regression analysis using SPSS version 16 software to process the data. The results showed that firm size had no significant positive effect on earnings management, profitability had no significant positive effect on earnings management, and leverage had no significant effect on earnings management. Keywords: Firm size, profitability, leverage and Earnings Management